1988
DOI: 10.1002/jnr.490190118
|View full text |Cite
|
Sign up to set email alerts
|

Immune response products alter CNS acitivity: Interferon modulates central opioid function

Abstract: The present report provides evidence to support the hypothesis that peptides released during an immune response alter CNS activity and thus may provide a means for the immune system to transmit afferent signals into the brain. Specifically, it is demonstrated that recombinant interferon-alpha (rIFN-alpha), a peptide associated with the immune response to viral infection, can alter opiate withdrawal severity in a dose-dependent manner upon direct injection into brain areas essential for this phenomenon. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…For example, recombinant human interferon-ac binds to opioid receptors and inhibits naloxone binding in brain membrane preparations of mice (Blalock & Smith, 1981) and rats (Menzies, Rier, Hall, O'Grady & Oliver, 1991), respectively. Interferon-a has opioid-like actions, such as attenuation of naloxone-induced withdrawal symptoms in morphinedependent rats (Dafny, Lee & Dougherty, 1988) and the induction of analgesia and catalepsy in mice (Blalock & Smith, 1981). Furthermore, it has been shown that interferon-a modulates the activity of temperature-sensitive neurones in the hypothalamic preoptic area (POA) (Nakashima et al 1988) and glucose-responsive neurones in the ventromedial hypothalamus (Kuriyama et al 1990) by its direct actions on opioid receptors of the cellular membranes in rat brain slice preparations, suggesting the mediation of interferon-cc-induced fever and anorexia by hypothalamic opioid receptors (Hori et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recombinant human interferon-ac binds to opioid receptors and inhibits naloxone binding in brain membrane preparations of mice (Blalock & Smith, 1981) and rats (Menzies, Rier, Hall, O'Grady & Oliver, 1991), respectively. Interferon-a has opioid-like actions, such as attenuation of naloxone-induced withdrawal symptoms in morphinedependent rats (Dafny, Lee & Dougherty, 1988) and the induction of analgesia and catalepsy in mice (Blalock & Smith, 1981). Furthermore, it has been shown that interferon-a modulates the activity of temperature-sensitive neurones in the hypothalamic preoptic area (POA) (Nakashima et al 1988) and glucose-responsive neurones in the ventromedial hypothalamus (Kuriyama et al 1990) by its direct actions on opioid receptors of the cellular membranes in rat brain slice preparations, suggesting the mediation of interferon-cc-induced fever and anorexia by hypothalamic opioid receptors (Hori et al.…”
Section: Discussionmentioning
confidence: 99%
“…Electrodes were fixed to the skull only when spike activity exhibited at least a 3:1 signal to noise ratio. When the neuronal activity exhibited less than 3:1 signal to noise ratio, the electrode was lowered in the steps of 10 μm increments until a 3:1 ratio spike activity was observed, to maximum depth of 7.4 mm below the skull (Chong et al, 2012; Claussen and Dafny, 2012; Dafny, 1980; 1982; Dafny et al,1988; Dafny and Terkel, 1990; Salek et al, 2012). The copper pins of all the electrodes were inserted into one Amphenol plug which was fixed onto the skull with dental acrylic.…”
Section: Methodsmentioning
confidence: 99%
“…During the placement of electrodes, the unit activity was monitored. Electrodes were fixed to the skull only when spike activity exhibited at least a 3:1 signal to noise ratio; Otherwise, the electrode was lowered in the steps of 10 μm increments until a 3:1 ratio spike activity was observed, to maximum depth of 6.6 mm below the skull (Chong et al 2012; Claussen and Dafny 2012; Dafny 1980, 1982, 1988; Dafny and Terkel 1990; Salek et al 2012). The copper pins were inserted into an Amphenol plug which was fixed onto the skull with dental acrylic cement.…”
Section: Methodsmentioning
confidence: 99%